2011
DOI: 10.1007/s11745-011-3570-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Guar Gum Reduces Lymph Flow and Diminishes Lipid Transport in Thoracic Duct‐Cannulated Rats

Abstract: Guar gum has a well-recognized hypolipidemic effect. This effect is thought to be due to the physicochemical properties of guar gum, which may cause changes in adsorption of lipids or the viscosity of the intestinal contents. Guar gum is a non-specific absorption inhibitor of any type of lipid-soluble compound. Permanent lymph duct cannulation was performed on rats to investigate the effects of dietary guar gum on lymph flow and lipid transport. Rats fed a 5% guar gum diet were compared with those fed a 5% cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The lower viscosity of the EW or EWH can indicate a higher dispersive activity in the digestive tract, which can be similarly observed in the case of a lipase inhibitor (e.g. water-soluble fiber) (21). It is possible that lower viscosity in the digestive tract leads to higher inhibition of lipid digestion and absorption because EW and EWH can have a higher dispersive activity in vivo.…”
Section: Resultsmentioning
confidence: 86%
“…The lower viscosity of the EW or EWH can indicate a higher dispersive activity in the digestive tract, which can be similarly observed in the case of a lipase inhibitor (e.g. water-soluble fiber) (21). It is possible that lower viscosity in the digestive tract leads to higher inhibition of lipid digestion and absorption because EW and EWH can have a higher dispersive activity in vivo.…”
Section: Resultsmentioning
confidence: 86%
“…However, it has also been reported that water-soluble dietary fiber does not involve SCFAs and suppresses fatty acid accumulation itself. For example, water-soluble dietary fiber may form a highly viscous matrix in the small intestine, increase the viscosity of the small intestine, and then physically suppress fat absorption [65,66]. These reports should be considered when investigating the association between gut microbiota and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The WHCs of casein, EWP, C-ph, and EWPph were measured as described previously. 24 Samples (0.1 g) were placed on two filter papers fitted in a stainless steel container (hole diameter, 2.5 cm; diameter, 5 cm; height, 1.5 cm) with a polypropylene net. This weight was measured as dry weight.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%